Penerapan Metode Multiple Scales untuk Masalah Galloping pada Mooring Cable FPSO - Arfi, Eristia; Utomo, Tri (Jurnal Ilmiah Soulmath : Jurnal Edukasi Pendidikan Matematika, 2019)
In essence, all objects in the universe have a natural frequency and when an object get an external force same with their natural frequency a resonance phenomenon will occur. In this study will be examined how the dynamic behavior of the mooring cable type Catenary Anchor Leg Mooring (CALM) on the Floating Production Storage Offloading (FPSO) when it gets external force with a very small frequency but near to the natural frequency itself. In the case of transmission cable, the phenomenon that describe this event is called the Galloping Phenomenon. The mathematics model of CALM system with the very small frequency will be solved using Multiple Scales method. The equilibrium point obtained is in the form of a center (stable). For negative, the amplitude value will be positive when the phase is zero (in-phase), at this condition if the initial conditions are chosen close enough to the equilibrium point then the cable will periodically oscillate with a limited phase value. Then if the initial conditions are selected a little further from the point of equilibrium, the cable will oscillate with amplitude the initial is the maximum amplitude and the value added of the dependent phase against time.